Female’s Silent Resistance against Hegemony in The Scarlet Letter, Bekisar Merah, and Belantik: A Comparative Analysis - RB. Edi Pramono (Humaniora, 2013)
Social patriarchy is a gender-biased hegemonic value that is structured for the benefits of men but unfortunately disadvantages women. Lasiyah, the protagonist of Bekisar Merah and Belantik, and Hester Prynne, the protagonist of The Scarlet Letter, experienced those hegemonic values that were oppressive, from their patriarchal societies i.e. Java and Puritans. By using the theories of both Hegemony and Comparative Literature, this discussion reveals the two protagonists’ similar silent resistance against the hegemonic values in that this brought them to become new persons with new personality and identity. They were similarly reborn. Both women had comparable factors driving them to conduct silent resistance: pride, dignity, and love. Woman, who is in general considered weak and powerless, is in fact strong and powerful.